fMRI investigation of response inhibition, emotion, impulsivity, and clinical high-risk behavior in adolescents - Brown, Matthew R. G.; Benoit, James R. A.; Juhás, Michal; Dametto, Ericson; Tse, Tiffanie T.; MacKay, Marnie; Sen, Bhaskar; Carroll, Alan M.; Hodlevskyy, Oleksandr; Silverstone, Peter H.; Dolcos, Florin; Dursun, Serdar M.; et al. (Frontiers in Systems Neuroscience, 2015)
High-risk behaviour in adolescents is associated with injury, mental health problems, and poor outcomes in later life. Improved understanding of the neurobiology of high-risk behaviour and impulsivity shows promise for informing clinical treatment and prevention as well as policy to better address high-risk behaviour. We recruited 21 adolescents (age 14-17) with a wide range of high-risk behaviour tendencies, including medically high-risk participants recruited from psychiatric clinics. Risk tendencies were assessed using the Adolescent Risk Behaviour Screen (ARBS). ARBS risk scores correlated highly (0.78) with impulsivity scores from the Barratt Impulsivity scale (BIS). Participants underwent 4.7 Tesla functional magnetic resonance imaging (fMRI) while performing an emotional Go/NoGo task. This task presented an aversive or neutral distractor image simultaneously with each Go or NoGo stimulus. Risk behaviour and impulsivity tendencies exhibited similar but not identical associations with fMRI activation patterns in prefrontal brain regions. We interpret these results as reflecting differences in response inhibition, emotional stimulus processing, and emotion regulation in relation to participant risk behaviour tendencies and impulsivity levels. The results are consistent with high impulsivity playing an important role in determining high risk tendencies in this sample containing clinically high-risk adolescents.